The Impact of Skill Exercises According to Self -efficacy Method on some Visual Perception Skills and the Learning of Shooting Skill in Basketball for Students - Shakir, Salam Musa (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This study aims to analyze the impact of skill-based exercises grounded in the self-efficacy approach on the development of visual perception among learners during the acquisition of the basketball shooting skill. Self-efficacy is a core psychological concept that reflects an individual's confidence in their ability to perform tasks and achieve goals, and it plays a fundamental role in enhancing both motor and visual performance. The problem of the study lies in the weakness of visual information processing among some learners, which leads to deficiencies in shape discrimination, distance perception, object recognition, figure-ground differentiation, as well as challenges in visual memory and spatial awareness. The researcher adopted an experimental methodology, dividing the sample into two groups: a control group and an experimental group. Standardized tests were administered to assess visual perception and shooting performance, and the data were analyzed using the SPSS statistical software. The results revealed statistically significant differences in favor of the experimental group, indicating that exercises based on the self-efficacy approach effectively enhanced learners’ perceptual, imaginative, and motor response abilities. These exercises also contributed to improving visual understanding through structured repetition, practical application, and interactive explanation. In light of these findings, the study recommends applying this training approach in other sports disciplines, given its positive impact on the development of visual and motor performance among learners.